2015
DOI: 10.17129/botsci.79
|View full text |Cite
|
Sign up to set email alerts
|

The grass family (Poaceae) in Coahuila, Mexico: Diversity and distribution

Abstract: Abstract:We analyzed the species richness of the grass family (Poaceae) in the state of Coahuila, Mexico, evaluating data from herbarium specimens. The evaluation was made by dividing the state into a grid of 20' × 20' squares (latitude × longitude), the objective was to identify areas of high species diversity. The herbaria revision documented 319 species of grasses, distributed in eight subfamilies, 19 tribes, and 97 genera. The genera with the highest number of species are Muhlenbergia (32 species), Boutelo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 19 publications
0
2
0
1
Order By: Relevance
“…The results from our field sampling suggested that the natural distribution of P. hallii is narrower than previously considered at the southern and eastern edges of the species distribution. Previous literature and collection records indicate that the natural distribution of P. hallii spans from the South-west USA (Oklahoma, Colorado, Texas, New Mexico and Arizona) through Mexico to the southern Mexican state of Oaxaca ( Gould 1975 ; Waller 1976 ; Herrera and Pámanes 2006 ; Estrada and Villareal 2010 ; Herrera-Arrieta and Cortés-Ortiz 2010 ; Sánchez-Ken 2011 ; Valdés-Reyna et al 2015 ). However, our collection efforts in the southern portion of this reported range, in the Mexican states of Mexico and Michoacán, failed to find P. hallii .…”
Section: Discussionmentioning
confidence: 99%
“…The results from our field sampling suggested that the natural distribution of P. hallii is narrower than previously considered at the southern and eastern edges of the species distribution. Previous literature and collection records indicate that the natural distribution of P. hallii spans from the South-west USA (Oklahoma, Colorado, Texas, New Mexico and Arizona) through Mexico to the southern Mexican state of Oaxaca ( Gould 1975 ; Waller 1976 ; Herrera and Pámanes 2006 ; Estrada and Villareal 2010 ; Herrera-Arrieta and Cortés-Ortiz 2010 ; Sánchez-Ken 2011 ; Valdés-Reyna et al 2015 ). However, our collection efforts in the southern portion of this reported range, in the Mexican states of Mexico and Michoacán, failed to find P. hallii .…”
Section: Discussionmentioning
confidence: 99%
“…Los tres géneros sustituidos son igualmente más característicos de regiones tropicales de escasa representación en la región NEMex; en contraste, Cyperus y Muhlenbergia contienen muchas especies características de pastizales y matorrales ampliamente representados en esta región. Resultados similares fueron encontrados por Valdés-Reyna et al (2015) al estudiar la familia Poaceae en Coahuila, quienes mencionan a Muhlenbergia como el género con la mayor riqueza de especies en el estado.…”
Section: Discussionunclassified
“…[19]. The genus Bouteloua comprising 29 species and 13 subspecies, is a dominant component of these ecosystems in Mexico [20]. Overgrazing by livestock is a widespread issue in northern Mexico [21,22].…”
Section: Introductionmentioning
confidence: 99%